2013
DOI: 10.1016/j.brainresbull.2012.10.011
|View full text |Cite
|
Sign up to set email alerts
|

βCCT, an antagonist selective for α1GABAA receptors, reverses diazepam withdrawal-induced anxiety in rats

Abstract: The abrupt discontinuation of prolonged benzodiazepine treatment elicits a withdrawal syndrome with increased anxiety as a major symptom. The neural mechanisms underlying benzodiazepine physical dependence are still insufficiently understood. Flumazenil, the non-selective antagonist of the benzodiazepine binding site of GABAA receptors was capable of preventing and reversing the increased anxiety during benzodiazepine withdrawal in animals and humans in some, but not all studies. On the other hand, a number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
1
10
1
Order By: Relevance
“…Using validated screening tests, we showed that the ligands display unique therapeutic profiles, including anxiolytic- and antidepressant-predictive properties, and pro-cognitive properties in GL-II-73, reversing stress-induced and age-related working memory deficits. The three novel ligands displayed reduced side effects compared to DZP (such as sedation and amnesia), consistent with reduced α1 potentiation [40-42]. …”
Section: Discussionmentioning
confidence: 89%
“…Using validated screening tests, we showed that the ligands display unique therapeutic profiles, including anxiolytic- and antidepressant-predictive properties, and pro-cognitive properties in GL-II-73, reversing stress-induced and age-related working memory deficits. The three novel ligands displayed reduced side effects compared to DZP (such as sedation and amnesia), consistent with reduced α1 potentiation [40-42]. …”
Section: Discussionmentioning
confidence: 89%
“…Flumazenil was used in the experiment because it is a nonselective antagonist of the benzodiazepine binding site of GABAA receptors (Divljakovi'c et al, 2013). Its administration assists in elucidating the mechanism of action of the formulation, since the possible decrease in anxiolytic effects in animals treated with flumazenil before receiving NMD-Lipo, and the resulting channel antagonism of benzodiazepines, is indicative of the action of nanoencapsulated nimodipine in such receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the suggested longer duration of action of βCCt (Zhang et al, 1995; June et al, 2003), its brain concentration of about 55 nmol/kg, measured 16 h after the last dose in protracted (twice daily for 14 days) administration of βCCt with diazepam (Savić et al, unpublished data), implies that βCCt in the present work was sufficient to prevent binding of diazepam at α 1 -containing GABA A receptors, without affecting the withdrawal behavior. Finally, it is noteworthy that in the current study the compounds were dissolved in the same solvent as used in our previous behavioral and pharmacokinetic studies (Divljaković et al, 2012; Divljaković et al, 2013; Savić et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Such an adaptive behavioral response was not observed in our previous studies, when the protracted i.p . administration of treatment has been also applied (Divljaković et al, 2012: Divljaković et al, 2013). The subtle differences in the experimental design, such as co-administration of two injections in the present, instead of one injection in previous studies, could have favored the development of the increased locomotion after 21 days of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation